2D Nanomaterials Processing and Integration in Miniaturized Devices - Pirri, Fabrizio; Cocuzza, Matteo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
2D nanomaterials are a relatively populous and ever-expanding class of innovative materials with disruptive potential for different application contexts. Although for some of them, such as graphene, various possible implementations have already been explored in different application fields, others, (e.g., Mxenes), are still relatively at an infantile stage with regard to handling, stability, exploitation, processing and practical use in devices and structures with higher dimensionality.In any case, regardless of the specific nature of each of these materials, their degree of purity and structure (mono-layers/few-layers/multi-layers) and their level of maturity, they all share the same challenges since their onset, such as processing, patterning, transfer and integration in devices, allowing smart exploitation of their unique properties, incorporation in matrices of different nature for the synthesis of nano-composites, and so on.Accordingly, this book aims to showcase research papers and review articles outlining recent progress and innovative approaches for 2D nanomaterials synthesis and/or processing, preparatory to their assembly or integration into devices, microstructures, microsensors and composites for different application fields.